Assessment of normal reference values for thyroid uptake of technetium-99m pertechnetate in a single centre UK population. Issue 9 (September 2018) - Macauley, Mavin; Shawgi, Mohamed; Ali, Tamir; Curry, Andrew; Howe, Kim; Howell, Elizabeth; Jefferson, Elizabeth; James, Andrew; Perros, Petros; Petrides, George S.
Abstract : Objective: This study aims to explore the normal reference values for thyroid uptake of technetium-99m ( 99m Tc) pertechnetate in a UK population. Patients and methods: A retrospective review of 60 euthyroid patients who underwent thyroid imaging with 99m Tc pertechnetate between January 2012 to April 2014 as part of dual-tracer subtraction parathyroid scintigraphy. 99m Tc pertechnetate thyroid uptake values were determined for each patient. Medical records and biochemical thyroid function tests were reviewed to ensure that all patients were not on medication that could affect thyroid function and they were both clinically and biochemically euthyroid 6 months before and following the scan. Results: Median and interquartile uptake range of 99m Tc pertechnetate in euthyroid patients were 0.9 and 0.5–1.4%, respectively. The normal reference range in the study population was 0.2–2.0%. Thyroid uptake inversely correlated with age in females ( r =−0.40, P =0.04), males ( r =−0.50, P =0.04), and whole group ( r =−0.40, P =0.002). Conclusion: The calculated normal reference range in this study was found to be less than that used in our own and many other UK institutions. The results demonstrate the importance of periodic evaluation of normal uptake values and provide support for prospective studies defining the normal reference range to be performed.